Senescence of intact plants leaves as the ecologically-rhythmic phenomenon - M. G. Aliev (Юг России: экология, развитие)
Senescence and life span of leaves are various at different plants. These phenomena depend on leave layers position and are under the genetic and endogenous control. Endogenous senescence differs at plants even within the limits of an individual on layers.